2007
DOI: 10.1021/cm7027178
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanocubes of Silicon with Zinc-Blende Structure

Abstract: Micro- and nanocubes of single-crystalline silicon with the zinc-blende structure have been synthesized by pulsed-laser-induced liquid–solid interface reaction. Raman scattering, scanning electron microscopy, transmission electronic microscopy equipped with energy dispersive X-ray spectrometer, selected area electron diffraction, and electron energy-loss spectroscopy are employed to characterize the morphology and structure of the as-synthesized samples. The first-principles calculations are employed to theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Liu et al suggested that the Raman shift seen for their larger sized silicon nanocubes (200-500 nm) was not due to the quantum size effect but instead attributed to the crystalline defects in the silicon cubes themselves. [31] Similarly, given the larger size of the silicon tetrahedra, we believe that the downshifted peak can also be contributed to crystalline defects, such as dislocations which were routinely observed under TEM and SEM analysis.…”
Section: Resultsmentioning
confidence: 86%
“…Liu et al suggested that the Raman shift seen for their larger sized silicon nanocubes (200-500 nm) was not due to the quantum size effect but instead attributed to the crystalline defects in the silicon cubes themselves. [31] Similarly, given the larger size of the silicon tetrahedra, we believe that the downshifted peak can also be contributed to crystalline defects, such as dislocations which were routinely observed under TEM and SEM analysis.…”
Section: Resultsmentioning
confidence: 86%
“…11b (from which 4 particles of the Si/Au core/shell NPs can be definitely identified). Figure 11d provides four examples of Raman spectra obtained from the Si/Au core/shell sample, condensed pure Au NPs reported elsewhere, 34,35 condensed Si NPs prepared by laser ablation in pure water, 36,37 The peak at 1089.0 cm −1 is attributed to a combination of the phenyl ring-breathing mode, C-H in-plane bending, and C-S stretching, 29 while the peak at 1579.9 cm −1 , which can be as attributed to the phenyl stretching motion, 40 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Sers Of An As-synthesized Single Si/au Core/shell Nanospherementioning
confidence: 92%
“…The Ag NPs colloidal solution is prepared by laser ablation in liquid, which is described in detail in our previous work. [32][33][34][35] Fig. 10 shows the bactericidal coefficients of Ag NDs and NPs with contacting times with bacteria of 30 s, 5 min and 30 min, respectively, at a concentration of 8 mg L À1 at room temperature.…”
Section: Antimicrobial Activity Of the As-synthesized Ag Ndsmentioning
confidence: 99%